Impact of an outright ban on the availability of commercial tanning services in Victoria, Australia. (1st August 2016) - Sinclair, C.; Cleaves, N.; Dunstone, K.; Makin, J.; Zouzounis, S.
Summary: Australian states have introduced an outright ban on commercial artificial tanning sunbeds. This was based on evidence from systematic reviews affirming a strong association between tanning bed use and increased risk of melanoma. The implementation of the ban provides an opportunity to assess the effectiveness of the legislation in preventing access to artificial UV radiation. Compliance with the ban has been enforced and monitored by government departments. We additionally monitored online tanning bed advertisements before and after the ban, showing a decline over time in the number of sunbeds advertised for sale on gumtree.com.au and ebay.com.au, from a peak of 115 advertisements in May 2014 to 50 or fewer per month from February 2015. There was also an increase in advertised price, with the percentage of sunbeds offered in Victoria on gumtree.com.au at higher than 2 000 increasing from around 25% between January and June 2014 to 65% in the quarter following the introduction of the ban. Advertisements on gumtree.com.au from individuals wishing to access a sunbed in a private home in Victoria increased from only isolated instances in the months immediately prior to the ban, to between 25 and 77 advertisements per month in the quarter following the ban. In summary, the introduction of an outright ban of commercial sunbeds has achieved a dramatic reduction in the availability of harmful artificial UV radiation sources in Australia. Long‐term benefits to the health of the population and a reduction in costs to the health system are expected to result.